2018
DOI: 10.7554/elife.37429
|View full text |Cite
|
Sign up to set email alerts
|

An intrinsic cell cycle timer terminates limb bud outgrowth

Abstract: The longstanding view of how proliferative outgrowth terminates following the patterning phase of limb development involves the breakdown of reciprocal extrinsic signalling between the distal mesenchyme and the overlying epithelium (e-m signalling). However, by grafting distal mesenchyme cells from late stage chick wing buds to the epithelial environment of younger wing buds, we show that this mechanism is not required. RNA sequencing reveals that distal mesenchyme cells complete proliferative outgrowth by an … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
43
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 43 publications
4
43
0
Order By: Relevance
“…Furthermore, in mouse embryos, inhibiting BMP signalling throughout limb buds by overexpressing Grem1 between E10.5 and E11.5 leads to the elongation of digits as well as the formation of both pre- and post-axial polydactylys 28 . In the limb buds, proliferation of mesenchymal cells terminates after the downregulation of Grem1 , and subsequently these cells undergo chondrogenic differentiation 17,29 . It is more likely that the avian digital pattern is regulated by the well-documented SHH/Gremlin1/AER-FGF feedback loops, in which Gremlin1 is the critical node linking each signalling module 10,1417 , and both intraspecific and interspecific variation in the digital pattern can be recognized as the expression pattern of Grem1 in early limb buds.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, in mouse embryos, inhibiting BMP signalling throughout limb buds by overexpressing Grem1 between E10.5 and E11.5 leads to the elongation of digits as well as the formation of both pre- and post-axial polydactylys 28 . In the limb buds, proliferation of mesenchymal cells terminates after the downregulation of Grem1 , and subsequently these cells undergo chondrogenic differentiation 17,29 . It is more likely that the avian digital pattern is regulated by the well-documented SHH/Gremlin1/AER-FGF feedback loops, in which Gremlin1 is the critical node linking each signalling module 10,1417 , and both intraspecific and interspecific variation in the digital pattern can be recognized as the expression pattern of Grem1 in early limb buds.…”
Section: Resultsmentioning
confidence: 99%
“…Cell cycle timers have been predicted in several developmental contexts (Newport and Kirschner, 1982; Durand and Raff, 2000; Burton et al, 1999; Primmett et al, 1989; Lewis, 1975). Recently, we provided evidence that a progressive increase in Bmp signalling is responsible for the slowing of the cell cycle (Pickering et al, 2018), which is linked to the acquisition of proximo-distal positional values in the distal mesenchyme of the chick wing bud (humerus to digit tips) (Saiz-Lopez et al, 2015). It is tempting to speculate that this could involve a D cyclin-dependent kinase inhibitor acting downstream of Bmp signalling, although it is unlikely to be p27 kip1 , which is only expressed in myogenic cells at later stages of chick wing development.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse, Grem1 expression is induced by Bmp4 and Shh signalling in the early bud (Benazet et al, 2009), and recent work in the chick (Pickering and Towers, 2016) and the mouse (Zhu et al, 2020 preprint) has shown that Grem1 expression becomes independent of Shh signalling following the early period of digit identity specification. In addition, grafts of distal mesoderm made between young and old chick wing buds have shown that the decline in the rate at which proliferation terminates proximo-distal outgrowth during the patterning phase is intrinsically controlled (Saiz-Lopez et al, 2015, and is associated with a progressive increase in Bmp signalling that overcomes Grem1 inhibition (Pickering et al, 2018) (Fig. 5).…”
Section: Limb Growthmentioning
confidence: 99%